Interest-parity conditions during the era of the classical gold standard (1880-1914): Evidence from the investment demand for bills of exchange in Europe - Nils Herger (Swiss Journal of Economics and Statistics, 2018)
This paper examines interest-parity conditions that arguably held as regards the investment demand for bills of exchange during the classical gold standard (1880-1914). Contemporaneous guides to the foreign exchanges report that close connections between the exchange and discount rates arose mainly with bills traded in London and the major financial centres on the European continent. As implied by the interest-parity condition, and in particular when future exchange-rate movements were covered by a suitable long-bill transaction, weekly data do suggest that between Paris, Amsterdam, Berlin, Brussels, and London, the return from discounting bills of exchange in the local money market was roughly equivalent to the return from investing in foreign currency bills.
Keywords: F31; N13; N23; 330; Bills of exchange; Exchange rates; Gold standard; Interest-parity condition